Pertalian Di Antara lokus Kuasa dan Pencapaian Akademik Murid-Murid Sekolah Rendah - Ismail, Maznah (Penerbit Universiti Sains Malaysia, 1987)
The study attempted to examine the relationship between locus of control and academic achievement of 4723 standard three pupils from urban and rural schools drawn throughout the country. In addition, the study also looked at several background variables such as, health of the pupils, preschool education, parental guidance, and socio-economl status of the family and their relationship with locus of control. The results supported t he findings of other studies which reveal a positive relationship between internal locus of control and academic achievement. Further, background variables mentioned above were found to correlate significantly with Internal orientation.